Nuclear Medicine in Thyroid Diseases in Pediatric and Adolescent Patients - Volkan-Salancı, Bilge (Mol Imaging Radionucl Ther, 2015)
Both benign and malignant diseases of the thyroid are rare in the pediatric and adolescent population, except congenital hypothyroidism. Nuclear medicine plays a major role, both in the diagnosis and therapy of thyroid pathologies. Use of radioactivity in pediatric population is strictly controlled due to possible side effects such as secondary cancers; therefore, management of pediatric patients requires detailed literature knowledge. This article aims to overview current algorithms in the management of thyroid diseases and use of radionuclide therapy in pediatric and adolescent population.